Asymptotic Behavior of the Kirchhoff Type Stochastic Plate Equation on Unbounded Domains - Xiaobin Yao; Zhang Zhang (Complexity)
In this paper, we study the asymptotic behavior of solutions to the Kirchhoff type stochastic plate equation driven by additive noise defined on unbounded domains. We first prove the uniform estimates of solutions and then establish the existence and upper semicontinuity of random attractors.